Analysis of the Application of Queue Theory in Ambacang Community Health Centers Padang - Hamna, Sukra; Ghina, Nadiyatul (Mathematical Journal of Modelling and Forecasting, 2026)
Community health centers (Puskesmas) play a crucial role in providing primary healthcare services. However, long patient queues often reduce service efficiency and patient satisfaction. This study analyzes queue performance at a Puskesmas outpatient clinic using the M/M/1 queuing model to evaluate waiting time and service effectiveness. Data were collected through seven days of field observations, recording patient arrival patterns and service times during operational hours. The results show that the patient arrival rate is patients per minute, while the service rate is patients per minute. The system operates under a stable condition with a utilization factor of . The average waiting time in the queue is minutes, whereas the total time spent in the system is minutes, indicating that a significant proportion of patient time is spent waiting for service. The originality of this study lies in its empirical application of the M/M/1 queuing model to a real outpatient healthcare system in a Puskesmas setting, providing practical performance indicators that can support operational decision-making in primary healthcare services. However, the study is limited by a relatively short observation period of seven days and data collected from a single healthcare facility, meaning the findings reflect local conditions and cannot be generalized to other healthcare centers with different operational characteristics. The study recommends improving workforce management and implementing a structured patient scheduling system to reduce waiting time and enhance service efficiency.